Apakah Program Keluarga Harapan Mampu Mengurangi Pekerja Anak di Masa Pandemi COVID-19? - Mohammad Maulana Ibrahim; I Dewa Gede Karma Wisana (Future Science, 2023)
The COVID-19 pandemic can be an economic shock for low-income households. Several studies have shown that child labor is a strategy used by households to cope with economic shocks. This shock will exacerbate the phenomenon of child labor. Social protection is a form of mitigating the impact of the COVID-19 pandemic which is considered able to reduce the number of child labor. Program Keluarga Harapan (PKH) is one of the social protection programs in Indonesia. This study investigates the impact of Program Keluarga Harapan (PKH) on the phenomenon of child labor during the COVID-19 pandemic. To overcome the problem of self-selection, this study applies the variable of interest as an endogenous variable. By using the recursive bivariate probit method, this study concludes that PKH has no impact on reducing the likelihood of a child becoming child labor during the COVID-19 pandemic. To enrich the research, we also investigated the influence of PKH on the phenomenon of child labor in the period before the COVID-19 pandemic and found that PKH had an impact on reducing the likelihood of a child becoming child labor in the period before the COVID-19 pandemic. Several factors that influence the phenomenon of child labor, such as the characteristics of children, the characteristics of the head of the household, household characteristics, and environmental characteristics, have been shown to influence a child's tendency to become child labor, both in both periods (before the pandemic or during the COVID-19 pandemic) and in only one period.